Cardiometabolic risk factors and their relationship with the interleukin-6 receptor gene polymorphism (rs2228145) in patients with hypertrophic cardiomyopathy - T. G. Bezhanishvili; A. Ya. Gudkova; V. G. Davydova; S. E. Andreeva; A. N. Krutikov; E. N. Semernin; B. N. Kudryavtsev; S. A. Pyko; A. A. Kostareva; E. N. Shlyakhto (Российский кардиологический журнал)
Aim. To analyze associations of interleukin-6 receptor gene (IL6R) polymorphism (rs2228145) with the clinical course characteristics of hypertrophic cardiomyopathy (HCM) in groups of patients with various cardiometabolic risk factorsMaterial and methods. The sample consisted of 123 patients with HCM. The age  of the included patients ranged from 18 to 91 years (59 [41; 66.5]), of whom 59 were men, 64 — women. Two age groups were identified: the first group included patients from 18 to 44 years old, the second — 45 years and older. The control group consisted of 200 people without cardiovascular diseases and other severe comorbidities.For genetic testing, DNA was isolated from peripheral blood lymphocytes. Genotyping of the IL6R gene polymorphism (rs2228145) was carried out by realtime polymerase chain reaction.Results. A significant prevalence of CC genotype of the IL6R gene polymorphism (rs2228145) was revealed in patients aged ³45 years compared with the control group, which occurred in 14,1% and 3,0% of cases, respectively (CC:AC+AA, odds ratio (OR), 0,885, 95% confidence interval (CI), 1,051-0,691, p=0,006), and insignificant prevalence of C allele in this group, which does not reach the level of significance (A:C, OR, 0,870, 95% CI, 0,427-1,02, p=0,06). The prevalence of CC genotype (15,1% vs 3,0%) and C allele (39,0% vs 29,0%) was revealed in patients with HCM in combination with hypertension (HTN) compared with the control group (CC:AS+AA, OR=0,174, 95% CI, 0,047-0,650), p=0,004); (A:C, OR=0,638, 95% CI, 0,406-1,002), p=0,05).Conclusion. The relationship between the IL6R gene polymorphism (rs2228145) and HTN in patients with HCM was confirmed. The presence of CC genotype and C allele of the rs2228145 IL6R gene polymorphism is significantly more common in patients with HCM with the disease onset ³45 years of age. The presence of CC genotype and C allele of the IL6R gene polymorphism (rs2228145) is associated with HTN in patients with HCM.